Current and emerging treatment options for ANCA-associated vasculitis: potential role of belimumab and other BAFF/APRIL targeting agents - Lenert A; Lenert P (Dove Medical Press, 2015)
Aleksander Lenert,1 Petar Lenert21Division of Rheumatology, University of Kentucky, Kentucky Clinic, Lexington, KY, USA; 2Division of Immunology, Department of Internal Medicine, The University of Iowa, Iowa City, IA, USAAbstract: Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) comprises several clinical entities with diverse clinical presentations, outcomes, and nonunifying pathogenesis. AAV has a clear potential for relapses, and shows unpredictable response to treatment. Cyclophosphamide-based therapies have remained the hallmark of induction therapy protocols for more than four decades. Recently, B-cell depleting therapy with the anti-CD20 antibody rituximab has proved beneficial in AAV, leading to Food and Drug Administration approval of rituximab in combination with corticosteroids for the treatment of AAV in adults. Rituximab for ANCA-associated vasculitis and other clinical trials provided clear evidence that rituximab was not inferior to cyclophosphamide for remission induction, and rituximab appeared even more beneficial in patients with relapsing disease. This raised hopes that other B-cell-targeted therapies directed either against CD19, CD20, CD22, or B-cell survival factors, B-cell activating factor of the tumor necrosis factor family (BAFF) and a proliferation-inducing ligand could also be beneficial for the management of AAV. BAFF neutralization with the fully humanized monoclonal antibody belimumab has already shown success in human systemic lupus erythematosus and, along with another anti-BAFF reagent blisibimod, is currently undergoing Phase II and III clinical trials in AAV. Local production of BAFF in granulomatous lesions and elevated levels of serum BAFF in AAV provide a rationale for BAFF-targeted therapies not only in AAV but also in other forms of vasculitis such as Behcet’s disease, large-vessel vasculitis, or cryoglobulinemic vasculitis secondary to chronic hepatitis C infection. BAFF-targeted therapies have a very solid safety profile, and may have an additional benefit of preferentially targeting newly arising autoreactive B cells over non-self-reactive B cells.Keywords: B-cell-activating factor of the TNF family, a proliferation-inducing ligand, antineutrophil cytoplasmic antibody-associated vasculitis, granulomatosis with polyangiitis, microscopic polyangiitis, B cells